2011
DOI: 10.1177/0907568210371526
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the bio-politics of childhood

Abstract: Telephone: +44 78 794 76065Navigating the bio-politics of childhood: How far can 'hybridity' take us? AbstractThe study of childhood is currently weakened by a biological/social dualism, separating 'social' from 'developmental' traditions and falsely identifying the investigation of life processes with the naturalisation of childhood. Researching the emerging space of childhood bio-politics, in which life processes are central to social and political processes, requires that these problems be managed. The view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 10 publications
(11 reference statements)
0
79
0
2
Order By: Relevance
“…Tellingly, in their analysis of hybrid childhoods, Lee and Motzkau (2011, 14) issue a warning about whether and how, "once researchers are engaged in, curious about or invested in such a topic and ready to recognize the full range of factors involved in it, how can that engagement be converted into manageable empirical questions?" For, once cognisant of different kinds of hybridity, it is unclear how (say, compared with different social constructions of childhood) those hybridities might be contrasted, or how those findings might be applied to different contexts (Lee and Motzkau 2011). In their view, the firm ground provided by either biological or social approaches is no longer sufficient in light of contemporary biopolitics.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Tellingly, in their analysis of hybrid childhoods, Lee and Motzkau (2011, 14) issue a warning about whether and how, "once researchers are engaged in, curious about or invested in such a topic and ready to recognize the full range of factors involved in it, how can that engagement be converted into manageable empirical questions?" For, once cognisant of different kinds of hybridity, it is unclear how (say, compared with different social constructions of childhood) those hybridities might be contrasted, or how those findings might be applied to different contexts (Lee and Motzkau 2011). In their view, the firm ground provided by either biological or social approaches is no longer sufficient in light of contemporary biopolitics.…”
mentioning
confidence: 93%
“…Second, in terms of children's geographers' articulation of 'multiplicities' in which spatial processes maybe invoked: I have suggested that two possible multiplicities might centre around questions of 'therapy' in alternative and mainstream education, and around the more-than-social emotional relations that have become the focus for attachment theories. Third, Lee and Motzkau (2011) do not account in any great depth for the experiences of children (nor do they purport to). It is here, then, that questions of 'voice' and 'agency' may return: as constituent elements in children's emotional geographies that go beyond, but do not seek to dismiss voice/agency as they appear in more-than-social relations.…”
mentioning
confidence: 99%
“…It takes its place in a context that is already replete with intergenerational conflict (Lee and Motzkau 2011). Its fresh contribution is to create locales in which 'drowning out' speech between young people is a near certainty.…”
Section: The 'Mosquito Teen Deterrent' and Biosocial Innovationmentioning
confidence: 99%
“…Such untimely meetings of age-related cochlear functioning and the contestation of public space that the device fosters also bring uncertainties however. Since its launch, vigorous media and legal campaigns aimed at banning the device have sought leverage in those uncertainties (Lee and Motzkau 2011). The device discriminates between old and young but does not discriminate within the set of those capable of hearing it.…”
Section: The 'Mosquito Teen Deterrent' and Biosocial Innovationmentioning
confidence: 99%
“…As we have suggested however, the biosocial imaginations that detain us do not have the structure of a self-consistent commitment or viewpoint. Instead they comprise sets of questions and qualities of curiosity that have value, local to circumstances, in orienting to and navigating the complex biosocial terrains of which humans are a part (Lee and Motzkau 2011). This structure ensures that the production of alternatives to dominant biosocial imaginations is more than a matter of conceptual critique.…”
Section: Resultsmentioning
confidence: 99%